Інтенсивність вільнорадикальних процесів у скелетних мʼязах щурів за умов різної забезпеченості раціону нутрієнтами - Voloshchuk, Oksana; Kopylchuk, Halyna (Bogomoletz Institute of Physiology National Academy of Sciences of Ukraine, 2022)
The intensity of free-radical processes in the skeletal muscles of rats at different dietary supply with protein and sucrose was studied. It has been established that the most pronounced intensification of free radical processes in the mitochondria of skeletal muscles is found in animals kept on a low-protein/ high-sucrose diet. In particular, the generation of superoxide anion-radical increases more than 5,3-fold and the generation of hydroxyl radical more than 3,2-fold compared with the control, more than a 14,3-fold increase in the carbonyl derivatives levels, and also decreases by three times in the free protein SH-groups levels against the background of a 1,7-fold decrease in catalase activity. It has been shown that excessive consumption of sucrose is a critical factor influencing the intensity of free radical processes in skeletal muscle mitochondria. The detected changes can be considered as prerequisites for skeletal muscle dysfunction under the conditions of nutrient imbalance.
INTENSITY OF FREE RADICAL PROCESSES IN RAT SKELETAL MUSCLES UNDER THE CONDITIONS OF DIFFERENT DIETARY SUPPLY WITH NUTRIENTS
Keywords: nutrients; skeletal muscles; reactive oxygen species; oxidative modification of proteins; antioxidant enzymes